Umbilical Cord Mesenchymal Stem Cell-Derived Small Extracellular Vesicles Deliver miR-21 to Promote Corneal Epithelial Wound Healing through PTEN/PI3K/Akt Pathway - Liu, Xiaolong; Li, Xuran; Wu, Guangyuan; Qi, Pengfei; Zhang, Yanyan; Liu, Zhiyu; Li, Xinyue; Yu, Yu; Ye, Xiangmei; Li, Yang; Yang, Dongguang; Teng, Yueqiu; et al. (Stem Cells International, 2022)
Objective. Rapid restoration of corneal epithelium integrity after injury is particularly important for preserving corneal transparency and vision. Mesenchymal stem cells (MSCs) can be taken into account as the promising regenerative therapeutics for improvement of wound healing processes based on the variety of the effective components. The extracellular vesicles form MSCs, especially exosomes, have been considered as important paracrine mediators though transferring microRNAs into recipient cell. This study investigated the mechanism of human umbilical cord MSC-derived small extracellular vesicles (HUMSC-sEVs) on corneal epithelial wound healing. Methods. HUMSC-sEVs were identified by transmission electron microscopy, nanoparticle tracking analysis, and Western blot. Corneal fluorescein staining and histological staining were evaluated in a corneal mechanical wound model. Changes in HCEC proliferation after HUMSC-sEVs or miR-21 mimic treatment were evaluated by CCK-8 and EdU assays, while migration was assessed by in vitro scratch wound assay. Full-length transcriptome sequencing was performed to identify the differentially expressed genes associated with HUMSC-sEVs treatment, followed by validation via real-time PCR and Western blot. Results. The sEVs derived from HUMSCs can significantly promote corneal epithelial cell proliferation, migration in vitro, and corneal epithelial wound healing in vivo. Similar effects were obtained after miR-21 transfection, while the beneficial effects of HUMSC-sEVs were partially negated by miR-21 knockdown. Results also show that the benefits are associated with decreased PTEN level and activated the PI3K/Akt signaling pathway in HCECs. Conclusion. HUMSC-sEVs could enhance the recovery of corneal epithelial wounds though restraining PTEN by transferring miR-21 and may represent a promising novel therapeutic agent for corneal wound repair.